TRUNK DISSOCIATION RETRAINER” FOR IMPROVING BALANCE, FUNCTIONAL ACTIVITIES AND GAIT IN HEMIPLEGIA. - ARUNACHALAM RAMACHANDRAN,; ANANDH VAIYAPURI,; JAGATHEESAN ALAGESAN,; RAJKUMAR KRISHNAN VASANTHI, (International Journal of Pharma and Bio Sciences, 2015)
Devising equipment for postural rehabilitation where the subjects can rehearse the movements with minimal physiotherapist guidance is must. Determine the effect of “Trunk Dissociation Retrainer” (TDR) in improving balance, functional activities and gait in hemiplegia. In this single blinded randomised controlled trial,56subjects were equally allotted by Simple random sampling into TDRGroup and Control group (CG). Berg balance scale(BBS), Functional Indipendent Measure scale(FIMS)and Gait velocity(GV) were used as outcome measures.Both groups were homogeneous at baseline. TDR group showed statistically significant improvement in the within group analysis for BBS, FIMSand GV with p<0.001.CG showed statistically significant improvement in the within group analysis for BBS, FIMS and GV p< 0.0001. TDR group showed statistically significant improvement than the CG in GVand FIMS with p<0.001 and BBS with p<0.007. TDR is a better alternative tool in improving balance, functional activities and gait in hemiplegia as compared to manual techniques.